Structural analysis of long arm excavator boom for optimization performance under maximum breakout condition - A. Rashid, Mohamad Syafiq; Chan, Chee Ming; Shaari, Muhammad Farid (Penerbit UTHM, 2020)
Long Arm Excavators are widely used in the construction site for excavating deep holes or trenches. However, due to the often-severe work conditions, such as large lifting loads, poor ground conditions to sustain the machine’s self-weight, Long Arm Excavator parts are subjected to constant wear and tear, incurring downtime losses and safety issues. The boom is considered the most critically affected part of the machine in these work conditions, where the high forces and unpredictable elements at the worksite could severely affect the machine’s overall performance. A potential solution is the reinforcement of the boom to improve its robustness. As an industrial collaborative project, the present study examines the performance of an existing machine with simulated improvement of the boom with such an approach, i.e. incorporation of stiffener reinforcement. Simulation works were carried out with Ansys Workbench 19.2 to assess the boom’s performance in terms of resulting stress, strain and deformation under a series of improved conditions, which include varying the dimensions and positions of the stiffeners on the boom. The improved conditions were Improvement I: stiffeners thickness reduction to 10mm, Improvement II: a combination of different stiffeners thickness reduction which 10mm and 8mm at critical and non-critical part of the boom, Improvement III: removal of half intermediate stiffeners thickness 12mm and Improvement IV: removal of half intermediate stiffeners thickness 8mm. Structural analysis was conducted based on the maximum breakout condition in which the excavator generates maximum digging force. From the analysis, it was found that the maximum equivalent stress of the boom decreased with the number of stiffeners. The combination of different stiffeners thickness could also increase the boom’s strength while decreasing the maximum equivalent stress. The lowest maximum equivalent stress of the boom was achieved via Improvement II with a reduction of 26.1% maximum equivalent stress. Removal of non-critical part stiffeners also kept stress values under the designated stress limits against fatigue failure, i.e. 44.49 MPa and 42.47 MPa (Improvement III and IV). In summary, the optimal design could be obtained with improvement II. This would effectively save on the manufacturing costs while maximizing the machine’s performance on-site, simultaneously reducing downtime and hence operating costs and time.